Georgian Bloomsbury - Rosenbaum, S. author. aut Link
XII, 253 p.
Keywords: Georgian Bloomsbury completes the literary history of Old Bloomsbury that began with Victorian Bloomsbury (1987) and continued with Edwardian Bloomsbury (1994). Covering the years between the First Post-Impressionist Exhibition and The First World War, the book describes and analyzes interrelated literary works by Roger Fry, Desmond MacCarthy, Clive Bell, E.M. Forster, Lytton Strachey, Leonard Woolf, and Virginia Woolf. The works considered include fiction, criticism, essays, and polemics as well as autobiography, journalism and literary history that members of the Bloomsbury Group wrote between 1910 and 1914.